Development of an Online Platform for Lesson Scheduling and Grade Management at MAN 1 Padang Using Waterfall Methodology - Surya Sahputra; Lativa Mursyida; Denny Kurniadi; Syukhri (Sagamedia Teknologi Nusantara, 2024)
This research focuses on developing an online platform for lesson scheduling and grade management at MAN 1 Padang using the Waterfall methodology. The platform adopts a structured Model-View-Controller (MVC) architecture to optimize efficiency and modularity, ensuring easier updates and maintenance. By utilizing Laravel as the framework and MySQL as the database, the system offers robust performance and scalability. The platform facilitates various administrative tasks, including lesson scheduling, grading, and real-time report access for students and parents, enhancing transparency and engagement. Blackbox testing results show high functionality across key performance areas such as content clarity, interface usability, navigation, security, and system responsiveness. This development aims to address inefficiencies in manual scheduling and grading processes, providing a streamlined, automated solution that improves overall academic management at MAN 1 Padang. The system is expected to increase the institution’s operational efficiency, contribute to better learning outcomes, and foster stronger communication between the school, students, and parents.